Peran Kepemimpinan Kepala Sekolah Dalam Implementasi Manajemen Berbasis Sekolah di SDIT Al Iman Bojonggede - Muhamad Meladih; Nanat Fatah Natsir; Amie Primarni (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2019)
The importance of the principal's role in managing and developing the quality of education in the education unit, a school if managed with good school management will certainly make the school a quality school and has a good output. This research aims to 1. To Know the Role of School Principals in Empowering SD IT AL IMAN Bojonggede teachers for the creation of a quality learning process, 2. To find out the Role of School Principals in establishing cooperation with the community / SD IT AL IMAN Bojonggede committees 3. To find out the Role of the Principal Schools in applying the principles of SBM in SD IT AL IMAN Bojonggede, 4. To find out the role of the School Principal in monitoring and evaluating SBM in SD IT AL IMAN Bojonggede, this study is descriptive qualitative, object studied by foundations, principals, teachers, staff and committee. The method of data collection is observation, interviews, and documents. The interactive data analysis model starts with data collection, data presentation, reduction and conclusion drawing. The results of this study indicate that 1. There is an effort from the School Principal in empowering and increasing the competence of SD IT AL IMAN Bojonggede teachers by holding seminars, training in motivational training by bringing in resource persons, following teachers in MGMP activities, 2. There is good collaboration between schools and community / commitment with the participation of the Community in school management and social activities. 3. In his leadership the school principals apply the principles of school-based management including independence of school staff in managing schools in various aspects, there is justice in school management, among which the headmaster is fair in deciding suatau permaslahan, being fair placement and assignment of teachers and staff, openness, the leadership of the school is open to all parties, including foundations, teachers / staff and the committee both in terms of administration and finance. 4. there is monitoring and supervision conducted by school principals in the application of school-based management among school program monitoring, administrative monitoring, learning monitoring, teacher and staff disciplinary monitoring.